Analisis Sikap Jujur Mahasiswa Dalam Menjalani Perkuliahan Di Kampus dan Di Luar Kampus - Sudarto Sudarto (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2023)
The purpose of this research is analyzing the honest attitude of the students in and out of the campus. This study uses a survey method with a quantitative approach. A sample of 16 students. Data analysis technique using percentage descriptive analysis. The results and conclusions of this research study were: (1) in living life on the campus, students were generally honest in terms of taking exams in the sense of not cheating and in completing assignments related to accessing data as they were, (2) in the behavior of returning the found items to campus, students are generally not honest, (3) in terms of plagiarism, students were generally honest, and (4) in everyday life students were generally honest in terms of admitting mistakes and expressing their feelings.